Diagnostic Accuracy of Different Immunological Methods for the Detection of Antineuronal Antibodies in Paraneoplastic Neurological Syndromes - Tampoia, M.; Zucano, A.; Antico, A.; Giometto, B.; Bonaguri, C.; Alessio, M. G.; Radice, A.; Platzgummer, S.; Bizzaro, N. (Immunological investigations, 2010)
The aim of this work was to evaluate the diagnostic accuracy of three different analytical methods for the detection of antineuronal antibodies and outline how they might be used to diagnose Paraneoplastic Neurological Syndromes (PNS) in a more effectively and rationally way. One hundred and four patients with neurological diseases were studied: 38 with paraneoplastic neurological disorder, 44 with other neurological diseases, and 22 with systemic autoimmune diseases and neurological disorders. 20 healthy subjects and 18 subjects with tumour without neurological disorders were also studied. Antineuronal antibodies were tested using three methods: Western blot (WB); Line-blot (LB); and indirect immunofluorescence (IIF) on primate cerebellum. The diagnostic sensitivity of the IIF, WB and LB methods was 28.9%, 26.3% and 36.8%, respectively, and their specificity was 95.2%, 97.1% and 98.1% respectively. The combined use of the three methods brought the sensitivity to 39.4%. The results of this study show that the methods used in clinical laboratories for the detection of antineuronal antibodies have good specificity. Among the three methods assessed, LB showed the highest diagnostic accuracy and also allowed for recognition of fine antibody specificities. According to these results we can suggest that LB should be used as the method of choice to search for paraneoplastic antibodies.